Consuming mathematics: John Ward's young mathematician's guide (1707) and its owners - Wardhaugh, B (Wiley, 2014)
John Ward's Young Mathematician's Guide appeared in fifteen impressions between 1707 and 1771; it was one of the most popular mathematical textbooks in Georgian Britain. This study examines the patterns of ownership and use that can be traced from surviving copies of the Guide and other evidence, to discover the kinds of reading and intellectual engagement the book received.